POLA SEBARAN DAN FAKTOR RISIKO KEJADIAN DBD DI KOTA KENDARI TAHUN 2010 - , I Kadek Mulyawan; , dr. Tri Baskoro Tunggul Satoto,M.Sc,PhD, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Dengue hemorrhagic fever (DHF) is a disease that is very alarming because it can cause death within a short time. Number of cases tends to rise and expanding distribution. Southeast Sulawesi Province including 12 provinces with a prevalence of clinical DHF above the national figure. In 2009, a total of six districts / cities in Southeast Sulawesi Province reported an incidence of dengue. One Kendari with reduced incidence rate of dengue cases by 117 per 100,000 population and the CFR of 1.34%. Larvae-free numbers in the city of Kendari is still below the national figure of 82%. The pattern of spread of dengue cases in the city of Kendari is not known with certainty. Objective: Knowing the pattern of distribution of dengue cases and the factors that influence the incidence of dengue in the city of Kendari Southeast Sulawesi Province in 2010. Research Methods: The study design was case-control and implemented in Kendari Southeast Sulawesi Province in 2010. The research sample is a population of patients diagnosed with dengue according to WHO criteria and documented in the DHF W2 Kendari City Health Department. The sample in this study as many as 276 people. Analysis of data with bivariabel analysis, multivariable and spatial. Results: There was no significant association between larva-free rate with the incidence of DHF (p: 0.62), there is a significant association between population density with DHF incidence (p: 0.00). There is a relationship between the behavior of people who do not do the PSN (OR: 2.81, CI: 1.70 to 4.81), there is a relationship between the habit of hanging clothes that have been used (OR: 2.89, CI :1,69-5 , 16), there is a relationship between the frequency of cleaning water reservoirs (OR: 3.45, CI: 1.73 to 7.49), there is a relationship between the presence of larvae (OR: 3.17, CI :1,81-5, 84). The dominant variables on the incidence of dengue in the city of Kendari is the frequency of cleaning water reservoirs (OR: 2.75, CI :1,29-5 .86). There is a clustering of dengue cases at 51 S coordinates 446725,9.55537 meters UTM with a residential area narrow. Conclusion: The grouping of cases of DHF occurred in dense residential areas with the most dominant risk factor affecting the incidence of dengue is the frequency of cleaning water reservoirs.